PERAN PEMERINTAH DAERAH DALAM PENGEMBANGAN EKOWISATA DI PERBATASAN KALIMANTAN BARAT – MALAYSIA - Muhammad Adib Alfarisi; Heriyanto (ADMIN: Jurnal Administrasi Negara, 2023)
Kapuas Hulu is part of the regional potential in Indonesia which has natural beauty and flora and fauna with natural potential to be exotic for tourists, which still looks beautiful and natural. However, there are several factors, such as inadequate access when traveling to the location, lack of global promotion, and governance that is still minimal with facilities by institutions. This shows that this research aims at BKSDA's efforts to protect nature as a role model for biodiversity with effective governance. Apart from that, this research uses qualitative research by describing work using factual data. Thus, the results of the research found that the increase each year dominates local tourists more than foreign tourists with data. There are also things that BKSDA collaborates to do, such as; 1. Become a government partner in encouraging and disseminating tourism awareness among the community. 2. Providing participation in various training related to understanding. what is tourism potential and also what it would be like to develop a tourist village like Lake Sentarum and Kapuas Hulu. 3. Mapping tourism potential, every tourist location point in Kapuas Hulu. 4. Create a tour package where this tour package has a tariff according to the tourist's trip in Kapuas Hulu and what the tourist activities will be in the future. 5. Promoting tourism products carried out by the regional government and BKSDA so that Lake Sentarum is internationally recognized. So that the existence of BKSDA and regional and central governments can provide support for managing biodiversity with regional potential as local community wisdom that can be developed as a tourist attraction.